Effects of Collagen Hydrolysates on Human Brain Structure and Cognitive Function: A Pilot Clinical Study - Koizumi, Seiko (Nutrients, 2019)
This study investigated the effects of collagen hydrolysates (CH) on language cognitive function and brain structure. In this open-label study, 5 g CH was administered once a day for 4 weeks to 30 healthy participants aged 49–63 years. The primary outcome measures were the brain healthcare quotients based on gray matter volume (GM-BHQ) and fractional anisotropy (FA-BHQ). The secondary outcome measures were changes in scores between week 0 and week 4 for word list memory (WLM) and standard verbal paired associate learning (S-PA) tests as well as changes in the physical, mental, and role/social component summary scores of the Short Form-36(SF-36) quality of life instrument. CH ingestion resulted in significant improvements in FA-BHQ (p = 0.0095), a measure of brain structure, as well in scores for the WLM (p = 0.0046) and S-PA (p = 0.0007) tests, which measure cognitive function. There were moderate correlations between the change in WLM score and the change in GM-BHQ (r = 0.4448; Spearman’s rank correlation) and between the change in S-PA score and the change in FA-BHQ (r = 0.4645). Daily ingestion of CH changed brain structure and improved language cognitive function.